Business and Community: Integrating Service Learning in Graduate Business Education - Wittmer, Dennis P. (Journal of business ethics, 2004)
For the past five years at the Daniels College of Business at the University of Denver a community service or service learning component has been included in the Values in Action class (now Values-Based Leadership), a core MBA course that integrates ethics, law, and public policy perspectives on business issues. This paper summarizes the educational philosophy and the mechanics of this required component. Few empirical studies have been conducted to gauge the perceived value and impact of a service learning requirement on students. Thus, several surveys were conducted to understand better the choices made by students as well as the impact of the requirement on students. Preliminary results reveal generally a positive effect on students, including some evidence that such a service learning requirement may influence students to make a greater lifetime commitment to community service.